Coevolution of specific gut microbiota of Min pig with host cold adaptation through enhanced vitamin B1 synthesis - Chang, Yang; Zhang, Ziwen; Cai, Jiancheng; Wang, Chunan; Liu, Di; Liu, Zhonghua; Xu, Chunzhu (Frontiers in Microbiology, 2024)
Min pigs exhibit remarkable cold tolerance, where vitamin B1 synthesis by gut microbiota is crucial for the host's energy metabolism. However, the role of this synthesis in cold adaptation of Min pigsare not yet fully understood. This study utilized 16S rRNA amplicon and metagenomic sequencing to examine seasonal variations in the gut microbiota of Min pigs. Results indicated a significant rise in microbial diversity in winter, with the Bacteroidetes group being the most notably increased. The vitamin B1 biosynthetic pathway was significantly enriched during winter, with six significantly upregulated genes (ThiC, ThiD, ThiE, ThiG, ThiH and ThiL) showing strong evidence of purifying selection. Among the six vitamin B1 synthesis genes significantly upregulated during winter, the increase was mainly due to a marked elevation in several sequences from specific microbial species.Binding energy analysis revealed that, except for ThiL, the average substrate binding energy of the top ten sequences with the largest seasonal differences was significantly lower than those of the ten sequences with the smallest differences. Furthermore, most of these sequences were uniquely prevalent in Min pigs and were not found in the homologous sequences of Duroc pigs. Bacteroidetes and Bacteroidales were identified as the primary contributors to these gene sequences. This research provides valuable insights for developing innovative cold-resistant feed and probiotics.